Make disruptive technological change happen - The case of additive manufacturing - Maresch, Daniela; Gartner, Johannes (Technological Forecasting and Social Change, 2020)
Disruptive technological change can contribute to a more abundant world. However, potentially disruptive technologies often struggle to significantly influence practice. One prominent example is additive manufacturing (AM). Although AM is often regarded as the next great technological revolution in waiting, it has not yet established itself on a large scale in many fields of application. We investigate the reasons behind those challenges by looking at the various fields in which AM is applied and relating them to the specific challenges AM faces, as well as the opportunities it offers in those fields. Our findings rely on a multi-perspective technology foresight process that is based on a discourse analytic approach and that comprises data tomography covering the biggest German-language online magazine on AM and qualitative interview data collected from a range of AM stakeholders. The findings provide an empirically well-founded evaluation and explanation of the link between the challenges and opportunities offered by AM and the extent to which this disruptive technology is leveraged in specific fields. The findings prompt recommendations on how new potentially disruptive technologies can foster abundance in traditional, well established market economies based on the example of the well-developed but traditional market economy of Austria.
Publisher Copyright: © 2018 Elsevier Inc. Copyright: Copyright 2020 Elsevier B.V., All rights reserved.
Keywords: 3D printing; Additive manufacturing; Discourse analysis; Technology foresight